Comparative study of the legal and regulatory framework of Islamic capital market in Maldives and Malaysia : a reform oriented analysis - Shujau, Mohamed (Kulliyyah Ahmad Ibrahim of Laws, International Islamic University Malaysia, 2021)
The study investigated and analyzed the legal and regulatory framework of Islamic capital market in Maldives, in contrast to the legal and regulatory framework of Islamic capital market in Malaysia. Maldives has no specific statutory provisions governing the country's Islamic capital market apart from a few regulations. On the contrary, Malaysia has a robust legal and regulatory framework, which is one of the significant factors that enables Malaysia to have the most developed Islamic capital market on the globe. Numerous provisions governing Islamic capital market in Malaysia are found in various statutes and multiple regulations issued by the regulator. Through comparative analysis of the legal and regulatory framework of Islamic capital markets in Maldives and Malaysia, the study proposed reforms in the legal and regulatory framework of Islamic capital market in Maldives. The study employed qualitative research methodology where data were collected from various government publications and interviews with relevant stakeholders in the industry. Research methods involved both doctrinal and non-doctrinal research. The findings suggested that when compared to Malaysia, Maldives requires amendments to several existing legislations and regulations, while new legislations and regulations need to be enacted. It is proposed to amend Maldives Securities Act 2006 to include Islamic securities and provide statutory recognition and binding powers to SharÊ'ah Advisory Council of Capital Market Development Authority. This study proposes to amend Maldives Monetary Authority Act 1981 to provide statutory recognition and binding powers to SharÊ'ah Council of Maldives Monetary Authority. In addition, it is recommended to amend Maldives Land Act 2002, Revenue Stamp Act 1970, and Maldives Companies Act 1996 to provide Islamic capital market investor friendly environment. Finally, it is indispensable to enact a trust companies act in Maldives.